Family income and young adolescents' perceived social position: associations with self-esteem and life satisfaction in the UK Millennium Cohort Study. Issue 10 (8th March 2016) - Bannink, Rienke; Pearce, Anna; Hope, Steven
Abstract : Background: Self-esteem and life satisfaction are important aspects of positive mental health in young people, and both are socially distributed. However, the majority of evidence is based on socioeconomic characteristics of the family. As children enter adolescence and gain independence, perceptions of their own social position are likely to influence mental health. Design and objectives: Using data on 11-year-olds from the UK Millennium Cohort Study, we investigated associations of both family income and young adolescents' perception of their social position with self-esteem and life satisfaction. We hypothesised that there would be differences in the impact of perceived social position on positive mental health when investigating the full scale scoring distribution or the bottom of the distribution. Therefore, we estimated proportional odds for having greater positive mental health (across the distribution of scores) and ORs for poor outcomes (lowest 10% scores). Results: The likelihood of greater self-esteem and life satisfaction increased with income; similarly, the risk of having poor self-esteem and life satisfaction increased as income decreased. Young adolescents who perceived their family as poorer than their friends (instead of about the same) were less likely to have greater self-esteem and life satisfaction and were more likely to have poor outcomes. Young adolescents who perceived their family as richer were more likely to have poor self-esteem, but were not less likely to have greater self-esteem. For life satisfaction, young adolescents who perceived their families as richer were less likely to have greater and more likely to have poor life satisfaction. Conclusions: Policies to redistribute income in families with children are likely to benefit the mental health of young people. However, it is also important to consider the impact of social comparison on young people's mental health as they enter adolescence.